Considerations on the fatigue assessment methods of floating-structure details. (August 2013) - Xu, Li; Lou, Benqiang; Barltrop, Nigel
The assessment of the finite element analysis results on stiffened plating structures is not straightforward because of the stress singularities that are inherent in the overall geometry. Some guidance is available but it is generally founded on limited comparisons with experiments rather than on an overall analysis of the problem, and the guidance is almost certainly not generally applicable. Fracture mechanics finite element methods are very useful but generally provide little understanding of the behaviour and a very limited basis for checking the quality of the results. This paper reports some work carried out recently to try to provide an understanding of the nature of the singularities in these details and some simple 'rules of thumb'. This provides a direct calculation method for fracture mechanics stress intensity factors and stress concentration factors for fatigue analysis based on the S–N approach (where S is the stress and N is the number of cycles to failure). By providing a better understanding of the nature of the stress fields, it also provides a good foundation for a finite element analysis of these details. This paper concentrates on the analysis of a simple planar right-angled cruciform corner with no bending, overlapping plates or weld reinforcement geometry. Also the effects of the mean stress and the residual stress are ignored. Some initial insights into the stress field are studied when the detail is not planar; this gives some further understanding of the behaviour of real structure details.